Targeting cholinergic dysfunction in Alzheimer’s disease: Development of next-generation galantamine derivatives - Zahra Keshavarz; Asadollah Hassankhani; Mehdi Yoosefian (Journal of Genetic Engineering and Biotechnology)
Alzheimer’s disease (AD) presents a significant and unmet medical need. Acetylcholinesterase (AChE) enzymes are key contributors to AD pathogenesis, instigating a cholinergic deficit and subsequent neurodegenerative progression, leading to neuronal loss and cognitive decline. This study leverages in silico methods to elucidate the structure–activity relationships (SAR) governing binding interactions and affinity between human AChE (hAChE, PDB ID: 4EY6) and potential novel ligands. Galantamine, a cornerstone cholinergic therapy for AD, serves as the template for the design of structurally diverse galantamine analogs. Employing rigorous molecular docking simulations and molecular dynamics simulations, these analogs exhibit promising potential for modulating the cholinergic system and mitigating cognitive dysfunction associated with AD. Our findings demonstrate the efficacy of computational drug design in developing superior galantamine analogs with enhanced target selectivity and potentially improved therapeutic profiles for AD patients, aiming to achieve superior cognitive outcomes and improved quality of life.